A Legacy of Energy Saving: The Discussion on Heritage Values in the First Programme on Energy Efficiency in Buildings in Sweden, c. 1974–1984. (2nd January 2019) - Legnér, Mattias; Leijonhufvud, Gustaf
ABSTRACT: The paper analyses the 'energy savings plan for existing buildings' (EBB) introduced in Sweden after the first oil crisis of 1973, and how effects of policies on the built heritage were perceived and communicated to a wider public. A conflict between conservation aims and energy efficiency was constructed for the first time in Sweden. The programme was a huge investment made by the government to reduce the import of oil. At first, little consideration was taken to the fact that heritage values might be at risk when giving property owners financial incentives to retrofit their houses. Soon increasing knowledge about the existing building stock showed that older houses were not necessarily energy inefficient. An information campaign launched by protagonists of building conservation encouraged property owners to direct measures to the interiors of buildings, thus saving the exterior character of not just single buildings but also complete neighbourhoods. Towards the end of EBB, the field of conservation had become a more articulated voice when it came to influencing measures aiming at increased energy efficiency. Finally, the paper discusses how values constituted in the 1970s affect policy and practice today.